2017
DOI: 10.1016/j.kint.2016.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor Nrf2 hyperactivation in early-phase renal ischemia-reperfusion injury prevents tubular damage progression

Abstract: Acute kidney injury is a devastating disease with high morbidity in hospitalized patients and contributes to the pathogenesis of chronic kidney disease. An underlying mechanism of acute kidney injury involves ischemia-reperfusion injury which, in turn, induces oxidative stress and provokes organ damage. Nrf2 is a master transcription factor that regulates the cellular response to oxidative stress. Here, we examined the role of Nrf2 in the progression of ischemia-reperfusion injury-induced kidney damage in mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
191
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 173 publications
(201 citation statements)
references
References 44 publications
7
191
2
1
Order By: Relevance
“…Even if treatment includes chronic administration of potent Nrf2 inducers, the body does not seem to be impaired. Indeed, many previous studies revealed that pharmacological Nrf2 activation has a protective effect on a variety of stress-mediated diseases, including kidney injury (80,81).…”
Section: Novel Function Of Nrf2mentioning
confidence: 99%
“…Even if treatment includes chronic administration of potent Nrf2 inducers, the body does not seem to be impaired. Indeed, many previous studies revealed that pharmacological Nrf2 activation has a protective effect on a variety of stress-mediated diseases, including kidney injury (80,81).…”
Section: Novel Function Of Nrf2mentioning
confidence: 99%
“…We recently investigated the roles that NRF2 plays in preventing kidney disease progression from AKI to CKD using a unilateral IRI mouse model [60]. We found that, compared to the contralateral uninjured kidneys, injured kidneys slightly induce the expression of NRF2 target genes within 24 h after injury and accumulate ROS and electrophiles.…”
Section: Evidence For the Beneficial Effects Of Nrf2 Activation In Thmentioning
confidence: 99%
“…2). The damaged area expands to the cortex, and the kidney mass is reduced after day 5, with the infiltration of inflammatory cells and tubular cell death [60]. On day 14, most of the remaining tubules are damaged, and progressive fibrosis is observed in the interstitium (Fig.…”
Section: Evidence For the Beneficial Effects Of Nrf2 Activation In Thmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Their renoprotective effects have been verified using Nrf2-deficient mice in, for instance, diabetic nephropathy, 20 lupus-like autoimmune nephritis 21 and ischemic reperfusion injury. 22 Bardoxolone methyl (BM), one such Nrf2 activator, has been reported in clinical practice to have a beneficial effect on the renal function of patients with type 2 diabetic nephropathy. 23 In hypertension models, Nrf2 activators were reported to be related to improvement of vascular function via antioxidant property.…”
Section: Introductionmentioning
confidence: 99%